La Asociación Global para el Desarrollo y su relación con la Ronda de Doha - Prado Lallande, Juan Pablo; Rosas, María Cristina (Revista Española de Desarrollo y Cooperación, 2023)
This article analyzes the main actions and results of the multilateral negotiations in the WTO, taking as a reference the Doha Round of Development. To achieve this objective, the article reviews the relationship between trade and development and the current situation of the Global Association for Development initiative. Finally, it focuses on the complexity of achieving the Eighth Millenium Goal due to the lack of will of the most powerful countries and of the international organizations alike.